Anterior composite restorations in clinical practice: findings from a survey with general dental practitioners - DEMARCO,Flavio Fernando (2013)
Objectives: The aim of this study was to assess technical preferences of general dental practitioners when restoring anterior composite restorations. How the level of clinical experience or post-graduate training infuenced their options was also tested. Material and Methods: A cross-sectional study was performed using a questionnaire with general dental practitioners (GDPs) (n=276) in Southern Brazil. Information regarding post graduation training (specialization, master's or PhD degree) and linical experience (years since completing graduation) were gathered. The options regarding anterior composite restorations (type of composite, adhesive system, light curing unit, polishing procedures and rubber dam use) were collected. Data were submitted to descriptive analysis and associations were tested. Results: Response rate was 68% (187). GDPs selected microhybrid composite (52%) and 2-step total etch adhesive system (77%). LED was the preferred method of activation for 72.8%. Immediate polishing was preferred by 75%, using a combination of techniques. Most of the respondents (74.3%) did not use rubber dam. More experienced clinicians used more halogen lights (p<0.022), performed more light monitoring (p<0.001) and were resistant to use rubber dam (p<0.012). Dentists with post-graduation training used 3-etch-and-rinse system more frequently (p<0.04), usually monitored light intensity (p<0.014) and placed rubber dam more frequently (p<0.044). Conclusions: Hybrid composite, simplifed adhesives, LED units and immediate polishing were preferred by Southern Brazilian dentists for anterior composite restorations. Few dentists used rubber dam to perform composite restorations in anterior teeth. Clinical experience and post-graduation training infuenced the dentists' choices.